ANTIVIRAL THERAPY IN LIVER CIRRHOSIS - P. O. Bogomolov; M. V. Matsievich; S. V. Koblov; M. Yu. Petrachenkova; K. Yu. Kokina (Alʹmanah Kliničeskoj Mediciny, 2016)
Management of patients with liver cirrhosis due to viral hepatitis is complicated; nevertheless, effective treatment is possible in the majority of diagnosed cases. Etiotropic treatment should be initiated as soon as liver cirrhosis is diagnosed. Antiviral therapy is the only evidence-based and justified treatment approach in such patients. Use of hepatoprotectors with doubtful efficacy significantly reduces chances of recovery and increases likelihood of poor outcomes. During the choice of antiviral regimen, considerations must be given to disease etiology and stage as well as liver functional status. Generally accepted scales for staging of liver cirrhosis (e.g. Child-Turcotte-Pugh and MELD) are helpful in the choice of up-to-date therapy regimen, assessment of the disease prognosis and planning of radical interventions.